Facile synthesis of copper cobalt sulfide and nickel hydroxide tube-like composites as battery-type active material of energy storage devices. (15th August 2023) - Kuo, Tsung-Rong; Fitriannisa, Istikhori; Chung, Ren-Jei; Lin, Kuan-Hsien; Yougbaré, Sibidou; Lin, Lu-Yin; Wu, Yung-Fu
Abstract: Bimetallic sulfide has attracted much attentions as efficient electroactive materials of battery supercapacitor hybrid (BSH), because of numerous redox states, high conductivity and good energy efficiency. Developing composites having excellent chemical and electrochemical properties is necessary to enhance the energy storage features of bimetallic sulfides. In this study, CuCo2 S4 and Ni(OH)2 composites (CuCo2 S4 @Ni(OH)2 ) are designed on Ni foam via the facial hydrothermal process and chemical bath deposition as the electroactive material of BSH at first time. Effects of Ni(OH)2 amounts on CuCo2 S4 on electrochemical and physical properties of CuCo2 S4 @Ni(OH)2 are investigated. The physical mixed CuCo2 S4 and Ni(OH)2 composite is also fabricated to verify synergistic effects of CuCo2 S4 @Ni(OH)2 . A higher specific capacitance (CF ) of 1583.9 F/g along with the capacity of 220.0 mAh/g are got for optimal CuCo2 S4 @Ni(OH)2 electrode, respectively comparing to 831.7 and 1063.3 F/g of CuCoS4 and Ni(OH)2 electrodes. A BSH is fabricated by the CuCo2 S4 @Ni(OH)2 electrode and the activated carbon electrode. The potential window of 1.6 V and maximum energy density of 32.1 Wh/kg at 1.1 kW/kg are achieved. The CF retention of 78% and Coulombic efficiency higher than 97% in 8000 charge/discharge cycles are also obtained for this BSH. Highlights: CuCo2 S4 @Ni(OH)2 are grown on Ni foam via hydrothermal and chemical bath deposition. Effect of Ni(OH)2 amount on physical and electrochemical properties are investigated. A higher CF value of 1583.9 F/g is got for CuCo2 S4 @Ni(OH)2 than CuCoS4 and Ni(OH)2 . Battery supercapacitor hybrid (BSH) shows energy density of 32.1 Wh/kg@1.1 kW/kg. BSH shows the CF retention of 78 % and Coulombic efficiency of 97 % in 8000 cycles.